2001
DOI: 10.1530/eje.0.1440021
|View full text |Cite
|
Sign up to set email alerts
|

Hyperleptinemia in women with Cushing's disease is driven by high-amplitude pulsatile, but orderly and eurhythmic, leptin secretion

Abstract: The episodicity of 24 h leptin release was studied in seven women (mean age 39 years, range 22±56 years) with pituitary-dependent hypercortisolism and in seven age-and body mass index (BMI)-matched female controls. Pulsatile leptin release was quantified by model-free CLUSTER analysis and deconvolution, the orderliness of leptin patterns by the approximate entropy statistic (ApEn), and nyctohemeral leptin rhythmicity by cosinor analysis. Blood samples were taken at 10 min intervals for 24 h. Both CLUSTER and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 61 publications
1
12
0
1
Order By: Relevance
“…These findings argue in favor of an unexpected synchrony between leptin and cortisol in CD, with a preservation of normal responsiveness of fat cells to cortisol, despite its excessive and dysregulated production in that disorder. This evidence supports a possible direct influence of hypercortisolemia on hyperleptinemia in CD, although the same group did not find any correlation between leptin and cortisol secretion rates [61] . Similarly, Weise et al [59] demonstrated maintenance of a normal diurnal leptin profile in 18 CS patients but did not observe any correlation between leptin and cortisol at any time point.…”
Section: Leptin and Cushing's Syndromesupporting
confidence: 55%
See 1 more Smart Citation
“…These findings argue in favor of an unexpected synchrony between leptin and cortisol in CD, with a preservation of normal responsiveness of fat cells to cortisol, despite its excessive and dysregulated production in that disorder. This evidence supports a possible direct influence of hypercortisolemia on hyperleptinemia in CD, although the same group did not find any correlation between leptin and cortisol secretion rates [61] . Similarly, Weise et al [59] demonstrated maintenance of a normal diurnal leptin profile in 18 CS patients but did not observe any correlation between leptin and cortisol at any time point.…”
Section: Leptin and Cushing's Syndromesupporting
confidence: 55%
“…A study of leptin pulsatility in 7 women with CD revealed a more than 2-fold elevation in daily leptin production rates as compared with age-, gender-and BMImatched controls, which was driven by higher pulse am-plitude rather than frequency [61] . Of note, approximate entropy of leptin release and cross-approximate entropy of cortisol and leptin were superimposable to those measured in controls.…”
Section: Leptin and Cushing's Syndromementioning
confidence: 99%
“…growth hormone; cortisol; insulin resistance; estradiol; ghrelin; thyroid hormones LEPTIN IS A CYTOKINE expressed by adipose tissue that suppresses appetite by interactions with its receptor in the brain (5, 32, 46). There is evidence that leptin is secreted in a pulsatile manner (20,22,44), but secretory dynamics of leptin are unclear, especially in adolescents. Low levels of leptin have been reported in adolescent girls with anorexia nervosa (AN) by our group (15,28,38) and by other investigators (17, 40).…”
mentioning
confidence: 99%
“…Finally, leptin might also be involved in the GH regulation. Circulating leptin concentrations in Cushing's syndrome are disproportionately increased compared with BMI-matched healthy controls (7,15,36). Short-term fasting in Cushing's syndrome did not restore normal leptin levels, and GH secretion remained blunted (19).…”
Section: Discussionmentioning
confidence: 86%